Don't just "sign"-- communicate! : a student's guide to ASL and the deaf community - Jay, Michelle (Los Angeles, CA : Judea Media, 2011)
This text gives the reader a better understanding of the ASL community and culture, as well as a better and more comprehensive understanding of learning the language.
Includes bibliographical references (p. 127-136) and index.
Keywords: American Sign Language -- Study and teaching; American Sign Language -- Study and teaching